The Prognostic Value of CRP/Alb Ratio in Predicting Overall Survival for Hepatocellular Carcinoma Treated with Transcatheter Intra-Arterial Therapy Combined with Molecular-Targeted Agents and PD-1/PD-L1 Inhibitors - Huang X; Peng G; Kong Y; Cao X; Zhou X (Journal of Inflammation Research)
Xiaoyu Huang, Gang Peng, Yaqing Kong, Xiaojing Cao, Xiang Zhou Department of Interventional Therapy, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100021, People’s Republic of ChinaCorrespondence: Xiang Zhou, Department of Interventional Therapy, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100021, People’s Republic of China, Email zhou.xiang@yeah.netPurpose: This study aimed to evaluate the prognostic value of C-reactive protein to albumin (CRP/Alb) ratio in hepatocellular carcinoma (HCC) treated with transcatheter intra-arterial therapy combined with molecular targeted agents (MTAs) and programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitors.Methods: Medical records of 271 consecutive patients with HCC receiving this combination therapy in China between 2019 and 2023 were retrospectively analyzed. Prognostic factors for progression-free survival (PFS) and overall survival (OS) were identified using univariate and multivariate Cox regression analyses. The discriminatory capability of inflammation-based prognostic scores—including the CRP/Alb ratio, C-reactive protein and alpha-fetoprotein in immunotherapy (CRAFITY) score, modified Glasgow prognostic score (mGPS), platelet-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII)—was assessed using the area under the curve (AUC).Results: A total of 133 patients met the inclusion criteria. The optimal cutoff value for the binary classification of CRP/Alb ratio in predicting OS, as determined using X-tile software, was 0.02. Multivariate analysis identified the CRP/Alb ratio (hazard ratio [HR] = 2.61, p < 0.001), tumor size (HR = 2.45, p = 0.018), and extrahepatic metastases (HR = 1.93, p = 0.015) as independent predictors of OS. For PFS, significant factors included Eastern Cooperative Oncology Group Performance Status (HR = 1.55, p = 0.033) and macrovascular invasion (HR = 1.48, p = 0.046). Patients with higher CRP/Alb ratios were more likely to experience fever and fatigue. The CRP/Alb ratio demonstrated significantly higher AUCs than PLR and SII at 24 months (all p < 0.05) and showed comparable AUCs to CRAFITY score and mGPS at 12, 24, and 36 months.Conclusion: The CRP/Alb ratio is a valuable prognostic marker for predicting OS and treatment-related adverse events in HCC patients receiving transcatheter intra-arterial therapy combined with MTAs and PD-1/PD-L1 inhibitors. This ratio can be used as a simple and reliable biomarker for assessing prognosis and guiding patient selection in clinical practice.Keywords: transarterial chemoembolization, hepatic artery infusion chemotherapy, targeted therapy, immunotherapy, inflammation, C-reactive protein